STRENGTHENING STUDENTS' SELF-REGULATORY CAPABILITY IN THE PROCESS OF MEMORIZING THE QURAN IN ISLAMIC BOARDING SCHOOLS - Suliyono Suliyono; Imron Rosyadi; Mohamad Zaenal Arifin (Institut Binamadani Indonesia, 2025)
This study aims to explain the dynamics of self-regulation possessed by students who memorize the Qur'an at the An-Nuqthah Islamic Boarding School, Tangerang. The research approach used is qualitative with a case study model implemented at the An-Nuqthah Islamic Boarding School, Tangerang. The primary sources of this study were seven students who memorize the Qur'an at the An-Nuqthah Islamic Boarding School, Tangerang, and involved the asatidz. Data collection techniques used interviews and observations. Checking the validity of the data used data reduction, data presentation and drawing conclusions. The results of the study show that: 1) Self-regulation in memorizing the Qur'an is carried out with a strategic planning strategy. Motivation is a key part of success in memorizing. Moral and ethical aspects as well as the ability to select and utilize the environment are crucial in the process of self-regulation of students who memorize the Qur'an at the An-Nuqthah Islamic Boarding School, Tangerang. 2) The self-regulation factors applied by the An-Nuqthah students greatly influence their emotional well-being. Behavioral aspects, including self-observation, have implications for morals, ethics, and social assessment, as well as the assessment of social skills. Furthermore, the environment also plays a significant role, with support provided by those closest to the students in their daily lives. This suggests that self-regulation and the emotional well-being of students memorizing the Quran are crucial to the process of memorizing the Quran